Jupiter's X-ray aurora during UV dawn storms and injections as observed by XMM–Newton, Hubble, and Hisaki. Issue 1 (2nd August 2021) - Wibisono, A D; Branduardi-Raymont, G; Dunn, W R; Kimura, T; Coates, A J; Grodent, D; Yao, Z H; Kita, H; Rodriguez, P; Gladstone, G R; Bonfond, B; Haythornthwaite, R P
ABSTRACT: We present results from a multiwavelength observation of Jupiter's northern aurorae, carried out simultaneously by XMM–Newton, the Hubble Space Telescope ( HST ), and the Hisaki satellite in 2019 September. HST images captured dawn storms and injection events in the far-ultraviolet aurora several times during the observation period. Magnetic reconnection occurring in the middle magnetosphere caused by internal drivers is thought to start the production of those features. The field lines then dipolarize, which injects hot magnetospheric plasma from the reconnection site to enter the inner magnetosphere. Hisaki observed an impulsive brightening in the dawnside Io plasma torus (IPT) during the final appearance of the dawn storms and injection events, which is evidence that a large-scale plasma injection penetrated the central IPT between 6 and 9 R J (Jupiter radii). The extreme ultraviolet aurora brightened and XMM–Newton detected an increase in the hard X-ray aurora count rate, suggesting an increase in electron precipitation. The dawn storms and injections did not change the brightness of the soft X-ray aurora and they did not 'switch-on' its commonly observed quasi-periodic pulsations. Spectral analysis of the X-ray aurora suggests that the precipitating ions responsible for the soft X-ray aurora were iogenic and that a power-law continuum was needed to fit the hard X-ray part of the spectra. The spectra coincident with the dawn storms and injections required two power-law continua to get good fits.